Inhibition of PI3K/Akt/mTOR overcomes cisplatin resistance in the triple negative breast cancer cell line HCC38 - Katharina Gohr; Alexandra Hamacher; Laura H. Engelke; Matthias U. Kassack (BMC Cancer, 2017)
Abstract Background Widely established targeted therapies directed at triple negative breast cancer (TNBC) are missing. Classical chemotherapy remains the systemic treatment option. Cisplatin has been tested in TNBC but bears the disadvantage of resistance development. The purpose of this study was to identify resistance mechanisms in cisplatin-resistant TNBC cell lines and select targeted therapies based on these findings. Methods The TNBC cell lines HCC38 and MDA-MB231 were subjected to intermittent cisplatin treatment resulting in the 3.5-fold cisplatin-resistant subclone HCC38CisR and the 2.1-fold more resistant MDA-MB231CisR. Activation of pro-survival pathways was explored by immunostaining of phospho-receptor tyrosine kinases. Targeted therapies (NVP-AEW541, lapatinib and NVP-BEZ235) against activated pathways were investigated regarding cancer cell growth and cisplatin sensitivity. Results In HCC38CisR and MDA-MB231CisR, phosphorylation of epidermal growth factor receptor (EGFR) and insulin-like growth factor 1 receptor (IGF1R) was observed. In HCC38CisR, treatment with NVP-AEW541 increased potency of lapatinib almost seven-fold, but both compounds could not restore cisplatin sensitivity. However, the dual phosphoinositide 3-kinase (PI3K) and mammalian target of rapamycin (mTOR) inhibitor NVP-BEZ235 acted synergistically with cisplatin in HCC38CisR and fully restored cisplatin sensitivity. Similarly, NVP-BEZ235 increased cisplatin potency in MDA-MB231CisR. Furthermore, NVP-AEW541 in combination with lapatinib restored cisplatin sensitivity in MDA-MB231CisR. Conclusion Simultaneous inhibition of EGFR and IGF1R in cisplatin-resistant TNBC cell lines was synergistic regarding inhibition of proliferation and induction of apoptosis. Co-treatment with NVP-BEZ235 or with a combination of NVP-AEW541 and lapatinib restored cisplatin sensitivity and may constitute a targeted treatment option for cisplatin-resistant TNBC.